Knowledge, Perception and Acceptance on Covid-19 Vaccine: A Systematic Review - Made Karma Maha Wirajaya; Putu Ika Farmani; Putu Ayu Laksmini (Future Science, 2022)
The COVID-19 disease first appeared in Wuhan City, Hubei Province, China. Until now, the disease was caused by the SARS-CoV-2 virus. This disease then spread to almost all countries and was declared a pandemic. One of the steps to prevent a wider spread is through vaccination. Acceptance of the COVID-19 vaccine has an important role in controlling the COVID-19 pandemic. The COVID-19 vaccine has a pretty good preventive effect, but its effectiveness really depends on the dose, disease severity, and type of COVID-19. Most people, including health workers, are not willing to receive the COVID-19 vaccine. The reason is the lack of knowledge and also the side effects of the vaccine, which affects the acceptance of the vaccine. The purpose of this study was to assess knowledge, perception and acceptance of the COVID-19 vaccine. This study uses a literature study approach and uses 4 review articles. Data were analyzed descriptively. The results of the analysis show that most people have insufficient knowledge about the COVID-19 vaccine. Perceptions of vaccines are also lacking because they feel unsure about the COVID-19 vaccine. Most health workers have good knowledge so that it is easier for them to accept the COVID-19 vaccine. The government needs to increase access to information about the COVID-19 vaccine so that people are willing to receive the COVID-19 vaccine.